The Coastal Iodine Paradox: A Narrative Review of Food Security and Dietary Patterns as Determinants of Iodine Status - Dwi Yuniar Intan Sari; Dila Lintang Harmanto Putri; Lilis Wijayanti; Suyatno Suyatno; Ahmad Syauqy (Journal of Health and Nutrition Research, 2026)
Iodine deficiency disorders (IDD) remain a persistent global public health concern, including in coastal regions traditionally assumed to have abundant iodine sources. The interrelationships between food security, dietary patterns, and iodine status in coastal populations are complex and not fully synthesized. To review and integrate international evidence on how food security shapes dietary patterns and influences iodine status among coastal populations. Methods: A structured search was conducted in PubMed, Science Direct, and Google Scholar for peer-reviewed articles published between 2015 and 2025. Keywords included iodine status, urinary iodine concentration, food security, dietary patterns, and coastal population. Studies were synthesized narratively, with thematic focus on links between household food access, dietary behavior, and measured iodine biomarkers. The review identifies a coastal iodine paradox, where proximity to marine resources does not ensure iodine sufficiency due to socioeconomic and food system constraints. Food security influences dietary diversity and intake of iodine-rich foods, while dietary patterns mediate iodine status. Ongoing nutrition transition, characterized by shifts toward processed foods, contributes to changing iodine intake. Variability in iodized salt use and fortification quality may lead to a dual burden of iodine deficiency and excess within the same population. Socioeconomic disparities, market access, and structural food system changes contribute to heterogeneity in urinary iodine concentration (UIC) and IDD prevalence. Iodine adequacy in coastal areas cannot be assumed based solely on geography. Integrated strategies addressing food security, dietary quality, and iodized salt monitoring are essential to ensure sustainable iodine nutrition in coastal communities.